Dukhūluṣ Ṣaḥāfah Ilā Ad-Dual Al-‘Arabiyyah Wa Ta’ṡīruhā ‘Alā Al-Mujtama’ Al-‘Arabī - Yuangga Kurnia Yahya (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2018)
The press is the oldest medium of modern media. Considering the new media which appeared in the last years, one might forget that the press itself was once a new medium and posed a challenge to the Arabic society as it is the case with the new media nowadays. Researching into the beginning of the press in the Arab countries is deeply interesting, especially with regard to the fact that this medium was not the only thing the French brought to Egypt under the command of Napoleon Bonaparte. In fact, they came with their culture and certain ideas that influenced the Arab societies until the present age. This article tries to give the reader an impression of these historical events that began with the French campaign in Egypt, in which Napoleon and his soldiers came with a printing machine. The followed method in this article is the descriptive as well as the analytical method. The researcher describes the events and circumstances of importance and continues with an analysis of the references he was able to investigate. He then presents the reader the results of his analysis. The researcher came to the conclusion that the press Napoleon initiated in Egypt did not have a real effect on the Egyptian society that went through a period of underdevelopment and a lack of knowledge. The researcher also came to the conclusion that Napoleon had experience with regard to the use and exploitation of the press for political purposes. He already used the press for his political propaganda in his campaign against Italy. The press that has been established by Muhammad Ali Pasha—27 years after the French had left Egypt and the press there came to a halt—was also not able to reach the heart of the Egyptian society. It rather reached certain members of the educated elite, but it remained until the present age—unlike the press that was established by Napoleon.